2020
DOI: 10.3390/w12113277
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Heavy Metals in the Surface Soil of the Region around the Qinghai Lake in Tibet Plateau: Pollution Risk Evaluation and Pollution Source Analysis

Abstract: In order to reveal the pollution characteristics and sources of heavy metals in surface soil of the region around the Qinghai Lake in Tibet Plateau, improve the prevention awareness and measures of local residents and urge the local government to implement necessary prevention and control measures, nine heavy metals (As, Cd, Co, Cr, Cu, Mn, Ni, Pb and Zn) in the surface soil samples of the region around the Qinghai Lake have been collected and analyzed. The methods such as statistic method, geo-accumulation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The formula for calculating the carcinogenic health risk index is as follows: where CR refers to the carcinogenic health risk index of metals in the exposure pathway, and SF is the carcinogenic slope factor (Cd: 6.1, As: 1.5) [ 38 ]. When CR < 1.0 × 10 −6 , it means that the metal has no carcinogenic risk; when 1.0 × 10 −6 < CR < 1.0 × 10 −4 , it means that the carcinogenic risk is acceptable; when CR > 1.0 × 10 −4 , it means the metal has carcinogenic risk.…”
Section: Methodsmentioning
confidence: 99%
“…The formula for calculating the carcinogenic health risk index is as follows: where CR refers to the carcinogenic health risk index of metals in the exposure pathway, and SF is the carcinogenic slope factor (Cd: 6.1, As: 1.5) [ 38 ]. When CR < 1.0 × 10 −6 , it means that the metal has no carcinogenic risk; when 1.0 × 10 −6 < CR < 1.0 × 10 −4 , it means that the carcinogenic risk is acceptable; when CR > 1.0 × 10 −4 , it means the metal has carcinogenic risk.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the burning of coal may also be a source of Cu, Ni, and Zn in soils around coal-fired power plants. Cr and As in soil are less contaminated by external sources and are most likely induced by natural processes such as weathering and erosion of sedimentary rocks [77]. Therefore, the first group is part of a mixed natural and anthropogenic source.…”
Section: Source Analysis Of Potential Toxic Pollutionmentioning
confidence: 99%
“…was identified as a major source of PTEs contamination in soil [78]. Specifically, Pb is a critical component of gasoline and diesel, and Pb from vehicle exhaust can infiltrate the soil following atmospheric deposition [77]. Furthermore, Cd is a common component of agricultural products such as herbicides and fertilizers [79].…”
Section: Source Analysis Of Potential Toxic Pollutionmentioning
confidence: 99%
“…Therefore, soil PTE pollution on the Qinghai–Tibet Plateau should not be ignored. Existing studies have mainly focused on investigating PTEs in Qingha-Tibet soils [ 4 , 23 , 24 ], glacial soils [ 25 ], railways [ 22 ], highways [ 15 ] and the litter catchment [ 26 ]. And found that the cryosphere (glaciers, permafrost, ice, and snow) was the essential source of PTEs during climate warming [ 27 ].…”
Section: Introductionmentioning
confidence: 99%